Physical Performance in the Health Environment: An Undervalued Practical and Inexpensive Tool - Jofre-Saldia, E (SAGE Publications Ltd, 2024)
In this article, Festa et al. highlight that the assessment of physical performance is not currently valued as a simple and practical tool for estimating health status in the general population. Consequently, the purpose of this opinion article is to highlight the importance of testing and classifying physical performance as an indicator of overall health, encouraging health professionals to consider them as an accessible and inexpensive tool for the public health context, in contrast to laboratory assessments. © Royal Society for Public Health 2024.